1937
DOI: 10.1084/jem.65.2.303
|View full text |Cite
|
Sign up to set email alerts
|

The Rapid Invasion of the Body Through the Olfactory Mucosa

Abstract: Clark (1) in 1929 described the introduction of Prussian blue into the nasal cavities of rabbits to determine the routes by which infectious agents pass from these cavities to the brain. At the earliest time of study, 1 hour after nasal inoculation of the pigment, granules were found between the cells of the olfactory mucosa, but not the respiratory, in the submucosa, the lymphatics and venules, in the perineural sheaths and between the fibers of the olfactory nerve, but not the trigeminal, and within the suba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

1938
1938
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…At this time point, bacteria were not isolated from the blood, effectively excluding a hematogenous route of CNS invasion. At 2 min postinfection, pneumococci were observed between the sustentacular cells of the olfactory epithelium, within the perineural space of the olfactory nerve, and within the subarachnoid space (329). Similar findings were reported by van Ginkel et al, who demonstrated that intranasally delivered S. pneumoniae (strain EF3030) could be recovered from nasal washes, the olfactory nerve and epithelium, and the olfactory bulb at 24 h postinfection in CBA/CAHN/xid mice (330).…”
Section: Pathogens That Enter the Brain Through The Nose Bacteriasupporting
confidence: 84%
See 1 more Smart Citation
“…At this time point, bacteria were not isolated from the blood, effectively excluding a hematogenous route of CNS invasion. At 2 min postinfection, pneumococci were observed between the sustentacular cells of the olfactory epithelium, within the perineural space of the olfactory nerve, and within the subarachnoid space (329). Similar findings were reported by van Ginkel et al, who demonstrated that intranasally delivered S. pneumoniae (strain EF3030) could be recovered from nasal washes, the olfactory nerve and epithelium, and the olfactory bulb at 24 h postinfection in CBA/CAHN/xid mice (330).…”
Section: Pathogens That Enter the Brain Through The Nose Bacteriasupporting
confidence: 84%
“…pneumoniae. Early studies by Rake demonstrated that S. pneumoniae rapidly enters the olfactory bulb in Swiss mice following intranasal inoculation (329). Remarkably, pneumococci were isolated from the olfactory bulbs of the brain at 1 min postinfection.…”
Section: Pathogens That Enter the Brain Through The Nose Bacteriamentioning
confidence: 99%
“…The two pathways are collectively called olfactory pathway, which have been confirmed by many studies. For example, Prussian blue was used to visualize the olfactory pathways after intranasal administration to rabbits and mice (7,8). The dye was observed in the olfactory mucosa and the perineural sheaths of the olfactory nerve, indicating that absorption across the epithelium was mainly associated with the olfactory cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Prussian blue was used to visualize the olfactory pathways after intranasal administration to rabbits and mice (7,8). The dye was observed in the olfactory mucosa and the perineural sheaths of the olfactory nerve, indicating that absorption across the epithelium was mainly associated with the olfactory cells (8). Jansson and Bjork (9) visualized the distribution of a 3 kDa fluorescein dextran (FD3) in the olfactory epithelium, the respiratory epithelium, the submucosa, the cribriform plate region and the olfactory bulb following nasal administration to rats using fluorescence microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Neither of the dyes used nor the HydrokoIIag, although left in the nOSe for as long as six hours, was found to pass through the cribriform plate and reach the interior of the cranium. Prussian blue, rapidly absorbed from the surface of the olfactory mucosa in mice (8), was found within two minutes in the tissue spaces, in blood and lymph vessels, in the perineural spaces of the olfactory nerve fibers, and in the sub arachnoid space and pia-arachnoid membrane. Horse serum, in stilled into the nose, was never detected in the cervical lymph of cats or rabbits.…”
Section: Of Lymphaticsmentioning
confidence: 99%